VOCATIONAL EDUCATION FOR A GREEN FUTURE (Innovative professional education, 2024)
The influence of sustainable development and, in particular, the «green transition» on professional education in the countries of the European Union has been studied. Achieving the goal of the «green transition» should lead to profound changes in theeconomy (the creation of a «circular economy»), technology, production, services, consumption and investment, which cannot be achieved without workers of certain qualifications with specific skills. In professional training and professional development,«green transition» means the development of «circular economy» skills, «skills for the green transition» and the formation of new systemic thinking. The role of work-based learning will be considered and its advantage for the «green transition» as it can provide students with the opportunity to develop «skills for the green transition».
Keywords: green transition, skills for a green transition, sustainable development, professional education, European Union, Ukraine